Inventory of Large Pelagic Fish from Java Sea Based on Fishermen’s Catches at TPI Kranji, Lamongan Regency – East Java - Andaresta, Olivia; Latuconsina, Husain; Zayadi, Hasan (Agrikan Jurnal Agribisnis Perikanan, 2024)
Fish Auction Place (TPI) is a means to market fish catches obtained by fishermen after going to sea, so it is one of the economic drivers in the capture fisheries sub-sector, also used as a data collection center for fish biological resources caught in one area as a support for capture fisheries statistics. One of the TPIs in Lamongan Regency, East Java is TPI Kranji, Paciran. This study aims to determine the number and species composition of large pelagic fish caught by fishermen. The research was conducted in September - October 2023, data collection was conducted 10 times. Data collection used survey methods, interviews and direct observation in the field. The results obtained were 3,983 individuals consisting of 8 species from 6 families, and 5 orders. The highest species composition and frequency of fish presence in Kranji TPI is gray tuna (Thunnus tonggol) 24.76% with 100% presence, and the lowest is lanjaman shark (Carcharhinus sealei) (0.05%) with 10% presence. The conservation status of the 8 species of fish caught varied greatly, including; Vulnerable (VE), Near Threatened (NT), Data deficient (DD), and Not Evaluated (NE), each represented by one species (12.5%), and as many as four species (50.0%) were categorized as Least concern (LC). The results of this study can serve as scientific information and evaluation material for further research on the biological aspects and dynamics of fish populations in measured fishing efforts to support sustainable utilization